Investigation of geochemical characteristics and hydrothermal alteration zone mapping supported by remote sensing of a porphyry copper prospect, southeastern Iran: integrated applications to exploration. Issue 4 (2022) - Khammar, Fereshteh; Joonaghani, Shahab Alborzian; Abadi, Leila Jan; Boomeri, Mohammad; Lentz, David R.
No abstract available